Exploring the Comparative Impact of Red and White Meat on Cardiovascular Diseases: A Global Cross‐Sectional Ecological Study - Wenpeng You; Shuhuan Feng; Frank Donnelly (Health Science Reports, 2025)
ABSTRACT Background The impact of white meat on cardiovascular diseases (CVDs) is rarely reported, while red meat has been extensively associated with CVDs. This phenomenon is worth exploring, considering that there is no substantial difference in composition between red meat and white meat. Methods Country‐specific data were extracted from United Nations agencies to analyse and compare the statistical roles of red meat and white meat in contributing to CVD incidence. Ageing, socioeconomic status, obesity, and urbanization were included as confounders in four data analysis models: bivariate correlations (Pearson's r and nonparametric), partial correlation, and stepwise linear regression. Results Globally, both red meat and white meat showed significant correlations with CVD incidence in bivariate analyses. However, when adjusting for confounders and the effect of red meat, red meat consistently maintained a significant association with CVD incidence, whereas the correlation for white meat became weak or negligible. These findings suggest that the apparent association between white meat consumption and CVD may be largely due to confounding by red meat intake. Conclusions Our analyses imply that red meat consumption exhibits a significantly stronger correlation with CVD incidence than white meat consumption. Although both meat types show significant associations in bivariate analyses, the association for white meat becomes negligible after adjusting for red meat intake and other confounding factors. This suggests that the adverse effects observed in studies that consider white meat consumption may be largely attributable to concurrent red meat consumption, rather than reflecting an independent risk from white meat.